The Right to a Fair Trial Within a Reasonable Time Under Burundian Law - Ndikumasabo, Noel (European Scientific Journal, ESJ, 2025)
In the course of a trial, both the speed of justice and its slowness present virtues and vices that are sometimes difficult to reconcile. From a doctrinal point of view, the temporality of the trial has been explored by various scholars, yet it remains a source of controversy. A fundamental conflict exists between modern proponents of celerity, who advocate for expedited proceedings, and traditionalists, who emphasize the quality of the trial and strict adherence to the rights of the defense. Given these divergent perspectives on trial temporality, between a rapid investigation and one conducted slowly and cautiously, the guarantee of reasonable time is the right solution for reconciling the two extremes of the temporality of the process: speed and slowness. To be in accordance with the concept of reasonable time, celerity must not be so fascinating as to disrupt the balance of power within the trial, undermine procedural formalism, or compromise the rights of the defense. It must be pursued with restraint, in concreto, ensuring that the time saved does not translate into a loss of quality. Although the Burundian Constitution enshrines the principle of the right to be tried within a reasonable time, the notion of reasonable time, as well as its assessment criteria, is not detailed in any legislative or regulatory text, nor is it enshrined in national case law. This gap sometimes leads to unreasonable delays in legal proceedings. In Burundian positive law, the tension between ensuring procedural quality, rooted in the right of defense, and the need for trial expediency, a common issue in well-established rule-of-law countries, is even more pronounced. There are divergent interpretations of the right to a fair trial within a reasonable time among judicial authorities. Some prioritize speed, minimizing delays in the proceedings, while others emphasize thoroughness and quality, ensuring strict adherence to the right of defense and the principle of adversarial proceedings, as enshrined in Article 39 of the Constitution. The development of the article emphasizes on clarifying the problem which affect the temporality of the trial and that of reconciling the speed and the quality of justice in Burundi. The results of this research are derived from doctrine, the jurisprudence of the Human Rights Committee, case law of the European Court of Human Rights and the African Court of Human and Peoples’ Rights, as well as Burundian case law. Through the analysis of doctrine, national and international case law, law and judgments, the study aims to evaluate how Burundian positive law reconciles the requirements of speed and those of length of procedures. The discussion of the results is based on a qualitative doctrinal research method. The documentary methodology analyzes legal texts, books, judgments, and rulings with the force of res judicata, along with national and international case law. This article seeks to examine the challenges and issues associated with the right to be tried within a reasonable time in Burundi. Its objectives is to analyze whether the guarantees proclaimed by the Constitution, the African Charter, and other international instruments ratified by Burundi, specifically those related to reasonable trial time, are effectively being implemented. It proposes how the international jurisprudence and its criteria that promote reasonable time can be endorsed in Burundian jurisprudence in order to provide a remedy for unreasonable delays in judicial proceedings. Given the advances made by the case law of the Human Rights Committee, the European Court, and the African Court regarding reasonable time, it is more essential than ever for Burundian positive law to foster a "culture of reasonable time" by reconciling, combining procedural guarantees and valorizing the criteria for good management of trial temporality. The implementation of reasonable time limits for judicial procedures can help to balance the course of the trial in Burundi. It may contribute to avoiding downtime of the trial, periods of inactivity, as well as unnecessary delays. It may also help the Burundian judicial and state authorities maintain control over the investigation process, remain clear-sighted, and serve as the ultimate guardian of both fairness and celerity.